Development of User Interface/User Experience using Design Thinking Approach for GMS Service Company - Bambang Suratno; Jihan Shafira (Journal of Information System and Informatics, 2022)
Information systems have an important role for firms to increase productivity. A service company located in Bontang, East Kalimantan, Indonesia (GMS), is engaged in scaffolding installation services and scaffolding rentals. The company has steadily experienced annual increase in the number of customers over the years. However, due to the still in manual-way of managing the scaffolding material, the increase of workload has also led to the increasing number of material handling human error cases and inefficient service processing time. As a company that provides B2B services, the management (user) then needs a website-based system for scaffolding material management that is tailored to their service operations and suits their special needs to support their operation. Thus, this study analyzes the suitable user interface/user experience using the Design Thinking method, which consists of 5 steps, namely Empathize, Define, Ideate, Prototype and Test. It serves as the initial phase of information system building to make sure that the design of the website based information system will suit the needs of their management. After conducting empathize stage using interview techniques and questionnaires and also conducting the define stage to gain insights on the required needs, it was known that the website system needed particular features, namely the availability of customer data, material data, user data, work partner data, transaction reports, invoices, integration with whatsapp and email, as well as a dashboard to visualize data such as the amount of material rented, available materials, and transaction history. In the prototype development stage, online UI/UX design tools are used. Using the prototype, the testing stage was then carried out, using the System Usability Scale (SUS) method. As a result, a value of 80.86 was obtained, meaning that the system created has good usability and can be used on an ongoing basis.